2009
DOI: 10.1534/genetics.109.106013
|View full text |Cite
|
Sign up to set email alerts
|

In Planta Mutagenesis Determines the Functional Regions of the Wheat Puroindoline Proteins

Abstract: In planta analysis of protein function in a crop plant could lead to improvements in understanding protein structure/function relationships as well as selective agronomic or end product quality improvements. The requirements for successful in planta analysis are a high mutation rate, an efficient screening method, and a trait with high heritability. Two ideal targets for functional analysis are the Puroindoline a and Puroindoline b (Pina and Pinb, respectively) genes, which together compose the wheat (Triticum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 51 publications
2
62
0
1
Order By: Relevance
“…Consequently, this protein is likely to be less stable than the others and therefore could affect grain hardness. In fact, similar changes have been found in PINs resulting in increased hardness (Feiz et al, 2009). To date, mutations at cysteine level in GSP-1 have only been detected by Wilkinson et al (2013) but not in Aegilops.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Consequently, this protein is likely to be less stable than the others and therefore could affect grain hardness. In fact, similar changes have been found in PINs resulting in increased hardness (Feiz et al, 2009). To date, mutations at cysteine level in GSP-1 have only been detected by Wilkinson et al (2013) but not in Aegilops.…”
Section: Discussionsupporting
confidence: 56%
“…The Trp-domain has been shown to be the most important region of both PINA and PINB, being essential to preserve the softness texture of grain (Feiz et al, 2009). The hydrophobic Trp residues show an affinity for polar lipids on the surface of starch granules (Pauly et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Puroindoline D1 genes have a dramatic impact on kernel texture, a significant effect on processing quality and may play a role in plant disease defense (Chen et al 2007;Feiz et al 2009;Morris 1997, 1998;Lillemo and Morris 2000;Ma et al 2009;Zhang et al 2010Zhang et al , 2011 Morris et al 2001;Xia et al 2005). In this study, we analyzed the frequency of PinaD1b and Pinb-D1b among four hard wheat groups (hard red winter, hard white winter, hard red spring and hard white spring), and found that 94 of 101 hard winter wheats (red and white) carried Pina-D1b (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenesis is an important tool in crop improvement to generate a vast amount of genetic variability for identification of improved or novel phenotypes that can be exploited in conventional plant breeding programmes and genetic studies (Parry et al, 2009). Induced mutations through non transgenic technique called Targeting Induced Local Lesions IN Genomes (TILLING) are now being widely used for developing improved crop varieties and for the discovery of genes controlling important traits and understanding the functions and mechanisms of actions of these genes in wheat Dong et al, 2009;Uauy et al, 2009;Feiz et al, 2009;. The range of alleles can be developed in a short time is matchless and unlikely to be found elsewhere in the pool of germplasm accessible to plant breeders, including land races and undomesticated relatives.…”
Section: Introductionmentioning
confidence: 99%